Eksperimentasi Elemen Tempo melalui Pengembangan Teknik Phasing dalam Karya Novena - Hery Kristian Buana Tanjung (Institut Seni Indonesia Denpasar, 2022)
Purpose: This study aims to determine the extent of the role of the element of tempo as an experimental material in the composition of the music of the work entitled novena. Research method: The research is carried out through the stages of the exploration process that is carried out up to the determination of experimental limits. Results and discussion: The composition technique used in the novena is the phasing technique, where this technique becomes an experimental tool in exploring the tempo element. Implication: Experimental limits need to be determined so that they do not become research bias, therefore an interpretive approach to sensory experiences or body sensations is needed when researchers pray the rosary, so that there is an interconnectedness between the research idea and the object used.